Arteriovenous access ischemic steal (AVAIS) in haemodialysis: a consensus from the Charing Cross Vascular Access Masterclass 2016. Issue 1 (January 2017) - Inston, Nicholas; Schanzer, Harry; Widmer, Matthias; Deane, Colin; Wilkins, Jason; Davidson, Ingemar; Gibbs, Paul; Zanow, Jeurgen; Bourquelot, Pierre; Valenti, Domenico
Arteriovenous access ischaemic steal (AVAIS) is a serious and not infrequent complication of vascular access. Pathophysiology is key to diagnosis, investigation and management. Ischaemia distal to an AV access is due to multiple factors. Clinical steal is not simply blood diversion but pressure changes within the adapted vasculature with distal hypoperfusion and resultant poor perfusion pressures in the distal extremity. Reversal of flow within the artery distal to the AV access may be seen but this is not associated with ischaemia in most cases. Terminology is varied and it is suggested that arteriovenous access ischemic steal (AVAIS) is the preferred term. In all cases AVAIS should be carefully classified on clinical symptoms as these determine management options and allow standardisation for studies. Diabetes and peripheral arterial occlusive disease are risk factors but a 'high risk patient' profile is not clear and definitive vascular access should not be automatically avoided in these patient groups. Multiple treatment modalities have been described and their use should be directed by appropriate assessment, investigation and treatment of the underlying pathophysiology. Comparison of treatment options is difficult as published studies are heavily biased. Whilst no single technique is suitable for all cases of AVAIS there are some that suit particular scenarios and mild AVAIS may benefit from observation whilst more severe steal mandates surgical intervention.